2013
DOI: 10.1016/j.celrep.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regulatory Layers of SREBP1/2 by SIRT6

Abstract: The NAD(+)-dependent protein deacetylase SIRT6 regulates genome stability, cancer, and lifespan. Mice overexpressing SIRT6 (MOSES) have lower low-density lipoprotein cholesterol levels and are protected against the physiological damage of obesity. Here, we examined the role of SIRT6 in cholesterol regulation via the lipogenic transcription factors SREBP1 and SREBP2, and AMP-activated protein kinase (AMPK). We show that SIRT6 represses SREBP1 and SREBP2 by at least three mechanisms. First, SIRT6 represses the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 35 publications
2
107
2
1
Order By: Relevance
“…16,17 Moreover, multiple investigations have revealed that SIRT6 regulates the pathogenesis of various types of cancers, such as including hepatocellular carcinoma, breast cancer, and pancreatic cancer. [18][19][20] Molecular mechanism exploration further indicates that the diverse roles of SIRT6 in carcinogenesis are implemented through the regulation of cellular signals including ERK, Smad, and Raf/mitogen-activated extracellular signal-regulated kinase/extracellular signal-regulated kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Moreover, multiple investigations have revealed that SIRT6 regulates the pathogenesis of various types of cancers, such as including hepatocellular carcinoma, breast cancer, and pancreatic cancer. [18][19][20] Molecular mechanism exploration further indicates that the diverse roles of SIRT6 in carcinogenesis are implemented through the regulation of cellular signals including ERK, Smad, and Raf/mitogen-activated extracellular signal-regulated kinase/extracellular signal-regulated kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…42 SIRT6, similar as NFkB, was a stress-responsive chromatin modifier, which shaped stress -related transcriptional networks. 43 Thus, we speculated that the down-regulation of miR-33b-3p by cisplatin treatment might probably through the SIRT6-mediated deacetylation in the promoter as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, a role for prolactin and serine/threonine protein kinase AKT1 in controlling the expression of SREBF1 was suggested (4). Additionally, the energy level in the diet may affect expression of SREBF1 as indicated by a recent study in mouse (68).…”
Section: Transcription Factors and The Control Of Milk Fat Synthesismentioning
confidence: 99%